Use of PCR-RFLP (Polymerase Chain Reaction - Restricted Fragment Length Polymorphism) in the gene of the enzyme Stearoyl-CoA-Desaturase in Bubalus bubalis - de Camargo, G. M.F. [UNESP]; Thomazine, R. B. [UNESP]; Boarini, L. [UNESP]; Camargo, F. G. [UNESP]; Lima, A. L.F. [UNESP]; Tonhati, H. [UNESP] (Taylor & Francis, 2007)
The milk is an important food because it contents Conjugated Linoleic Acids (CLA). These fatty acids are synthesized in mammary gland under action of the enzyme Stearoyl CoA-Desaturase (SCD) and have showed some positive effects in human disease prevention and treatments. A variation of CLA in milk fat exists and can be partially explained by the different levels of expression of SCD. The aim was to study part of the encoding regions of SCD's gene using PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism). Genomic DNA was extracted from lactating Murrah females. After this, PCR reactions were made by using primers Z▶◀D1 that encloses exon I, II and intron I. The fragments amplified are composed by 938 pb. Then, RFLP techniques were applied in the fragments using the restriction enzymes Pst I and Sma I. The enzyme Pst I has generated fragments of 788pb and 150bp and the Sma I has generated fragments of 693pb and 245pb. All the animals showed the same migration standard for both enzymes, characterizing a genetic monomorphism for this region of SCD gene. The analysis determined that there aren't genetic differences between these animals in the studied regions by using Pst I and Sma I enzymes.
Keywords: CLA; PCR; RFLP; Stearoyl-CoA-Desaturase